EFFECT OF SOCIAL ACCEPTANCE ON QUALITY OF LIFE AMONG ORTHOPEDICALLY DISABLED STUDENTS FROM INCLUSIVE AND SPECIAL INSTITUTES - Sultan, Bukhtawar; Atta, Mohsin; Malik, Najma Iqbal (Journal of Postgraduate Medical Institute, 2018)
Objective: To explore the impact of social acceptance on quality of life among orthopedically disabled students from special and inclusive institutes. Methodology: Sample composed of 150 orthopedically disabled students from special (n= 75) and inclusive institutes (n= 75) of Sargodha, Rawalpindi, Khushab and Jhelum districts from December, 2014 to June, 2015 and was selected through purposive sampling technique. WHO Quality of Life Scale (Urdu version)1 and Scale of Social Acceptance were used as study tools. Results: Age range students was 12 to 35 (M= 17.11 ±4.71) years. Social acceptance was a strong predictor of quality of life among physically disabled students of special institutes show-ing the beta value (Î²= .54, t= 5.5, p <.001). Social skill was the most significant component of social acceptance in posi-tively predicting quality of life showing the beta value (Î²= .69, t= 8.52, p< .001). Student behavior and peer attitude sub-scales was found to be non-significant predictors of quality of life. Significant mean differences were found in QoL {t (148)= 2.80, p <.006} where students from inclusive institutes have high level of QoL as compared to special institute students (M= 80.66 ±16.73). Significant differences were also observed on physical {t (148)= 2.95, p <.004} and psycho-logical functioning {t (148)= 3.35, p <.001}. . Conclusion: Student from inclusive institutions tend to have better quality of life and social acceptance as compared to those from special institutions.